Recognition of Hydrophilic Cyclic Compounds by a Water-Soluble Cavitand - Wan, Yun-Hui (Molecules, 2021)
A water-soluble deep cavitand bearing amides on the upper rim and trimethyl ammonium groups on the feet was synthesized. The open-ended cavity is stabilized by the intramolecular hydrogen bonds formed between the adjacent amides, and the introduction of trimethylammonium imparts to the cavitand good solubility in water. The cavitand exhibits high binding affinity and selectivity to hydrophilic molecules in water. With certain guests, such as cyclohexyl alcohols, amines and acids, the recognition involves the synergistic action of hydrogen bonding with hydrophobic effects. The binding phenomena are interpreted in terms of a fixed solvent cage presented by the host to the guest.